136k views
0 votes
PLEASE HELP

divide. (3x-2)(x-4)-(x-4)(6-5x)
/(4-x)(8x-1)​

User Madav
by
4.5k points

1 Answer

5 votes

Answer:

x = 39/74 - sqrt(1817)/74 or x = 39/74 + sqrt(1817)/74

Explanation:

Solve for x:

(x - 4) (3 x - 2) - ((6 - 5 x) (x - 4) (8 x - 1))/(4 - x) = 0

Simplify and substitute y = 4 - x.

(x - 4) (3 x - 2) - ((6 - 5 x) (x - 4) (8 x - 1))/(4 - x) = -434 + 257 (4 - x) - 37 (4 - x)^2

= -37 y^2 + 257 y - 434:

-37 y^2 + 257 y - 434 = 0

Divide both sides by -37:

y^2 - (257 y)/37 + 434/37 = 0

Subtract 434/37 from both sides:

y^2 - (257 y)/37 = -434/37

Add 66049/5476 to both sides:

y^2 - (257 y)/37 + 66049/5476 = 1817/5476

Write the left hand side as a square:

(y - 257/74)^2 = 1817/5476

Take the square root of both sides:

y - 257/74 = sqrt(1817)/74 or y - 257/74 = -sqrt(1817)/74

Add 257/74 to both sides:

y = 257/74 + sqrt(1817)/74 or y - 257/74 = -sqrt(1817)/74

Substitute back for y = 4 - x:

4 - x = 257/74 + sqrt(1817)/74 or y - 257/74 = -sqrt(1817)/74

Subtract 4 from both sides:

-x = sqrt(1817)/74 - 39/74 or y - 257/74 = -sqrt(1817)/74

Multiply both sides by -1:

x = 39/74 - sqrt(1817)/74 or y - 257/74 = -sqrt(1817)/74

Add 257/74 to both sides:

x = 39/74 - sqrt(1817)/74 or y = 257/74 - sqrt(1817)/74

Substitute back for y = 4 - x:

x = 39/74 - sqrt(1817)/74 or 4 - x = 257/74 - sqrt(1817)/74

Subtract 4 from both sides:

x = 39/74 - sqrt(1817)/74 or -x = -39/74 - sqrt(1817)/74

Multiply both sides by -1:

Answer: x = 39/74 - sqrt(1817)/74 or x = 39/74 + sqrt(1817)/74